Redistribution around the world: Causes and consequences - Markus Jäntti; Jukka Pirttilä; Risto Rönkkö (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2016)
This paper re-examines the determinants and consequences of redistribution in light of improved data and methods relative to earlier literature. In particular, we use the latest version of the UNU-WIDER' Income Inequality Database to have the best available estimates of both pre- and post-redistribution inequality for the largest set of countries and periods. We also tackle head-on problems of related to model specification that risks generating large biases in estimates because of mechanical associations between variables. The paper also shows how earlier results on the determinants of redistribution and the impacts of redistribution on growth can be misleading.
Keywords: H11; O11; O47; 330; cross-country analysis; growth; inequality; redistribution